Η χρήση αναβολικών ουσιών ως καίριο πρόβλημα του σύγχρονου αθλητισμού, και οι απόψεις των φοιτητών/τριών του ΤΕΦΑΑ Παν/μίου Αθηνών - Πολυδωρόπουλος, Κ.; Γογγάκη, Κ.; Μαυροδάκος, Π. (http://archive-gr.com/gr/p/pepfa.gr/2013-09-16_2866954-titles_6, 2011)
(2011). Doping as a major problem in modern sport and the views of the Sport Physical Education Department of the University of Athens students. Polydoropoulos Konstantinos, Konstantina Goggaki, and Panagiotis Mavrodakos. The championship has now become professional and high ideals sometimes replaced by an effort to maximize profit. Throughout the world, doping is an illegal act, which is treated with sentences. However, the problem, can not be limited to repression and criminalization of doping, but mainly on prevention. This study presents the students’ views in relation to doping in modern sport. Their view seems to be of great value as they are in majority, modern athletes and future physical education teachers, both in education and in training sessions clubs.  Students' views recorded through questionnaire. The results appear to be quite encouraging as only a small percentage of students   have used anabolic substances. Quite interesting is the emergence of the fact of doping without a scientific supervision. The survey reveals that most of those who use anabolic substances have been supplied either by themselves or by a shop selling sportswear, either through a gym, either via the internet, or by their coach while few seem to have been supplied through their Sports Doctor.   Keywords: competitive sport, banned substances, use, questionnaire studen *** Απόσπασμα Έρευνας που διεξήχθη στο πλαίσιο της Γραμματείας Επιτροπής Ερευνών του Εθνικού και Καποδιστριακού Πανεπιστημίου Αθηνών με Επιστημονική Υπεύθυνη την Επίκουρη Καθηγήτρια Κων/να Γογγάκη και με θέμα: «Οι απόψεις των φοιτητών/τριών του ΤΕΦΑΑ Αθηνών σχετικά με τη χρήση, την πρόθεση χρήσης και τις ηθικές διαστάσεις της χρήσης των αναβολικών ουσιών στον αθλητισμό».  http://archive-gr.com/gr/p/pepfa.gr/2013-09-16_2866954-titles_6 http://www.pepfa.gr/index.php?option=com_content&view=article&id=163:polydoropoulos-konstantinos-konstantina-goggaki-and-panagiotis-mavrodakos&catid=56:teyxos-2013&Itemid=54